Community methicillin-resistant Staphylococcus aureus outbreaks in areas of low prevalence. - Bellis, Katherine L; Dissanayake, Oshani M; Harrison, Ewan M; Aggarwal, Dinesh (Elsevier BV, 2025)
BACKGROUND: Community-acquired (CA), community-onset methicillin-resistant Staphylococcus aureus (CO-MRSA) infection presents a significant public health challenge, even where MRSA rates are historically lower. Despite successes in reducing hospital-onset MRSA, CO-MRSA rates are increasing globally, with a need to understand this trend, and the potential risk factors for re-emergence. OBJECTIVES: This review aims to explore the characteristics of outbreaks of community-acquired community-onset methicillin-resistant Staphylococcus aureus in low-prevalence areas, to understand the factors involved in its rise, and to translate this knowledge into public health policy and further research needs. SOURCES: PubMed, EMBASE, and Google Scholar were searched using combinations of the terms 'transmission', 'acquisition', 'community-acquired', 'MRSA', 'CA-MRSA', 'low prevalence', 'genomic', 'outbreak', 'colonisation', and 'carriage'. Wherever evidence was limited, additional articles were sought specifically, via PubMed searches. Papers where materials were not available in English were excluded. CONTENT: Challenges in defining low-prevalence areas and the significance of exposure to various risk factors for community acquisition, such as healthcare settings, travel, livestock, and environmental factors, are discussed. The importance of genomic surveillance in identifying outbreak strains and understanding the transmission dynamics is highlighted, along with the need for robust public health policies and control measures. IMPLICATIONS: The findings emphasise the complexity of CO-MRSA transmission and the necessity of a multifaceted approach in low-prevalence areas. This includes integrated and systematic surveillance of hospital-onset-, CO-, and livestock-associated MRSA, as has been effective in some Northern European countries. The evolution of CO-MRSA underscores the need for global collaboration, routine genomic surveillance, and comprehensive antimicrobial stewardship to mitigate the rise of CO-MRSA and address the broader challenge of antimicrobial resistance. These efforts are crucial for maintaining low MRSA prevalence and managing the increasing burden of CO-MRSA in both low and higher prevalence regions.
Keywords: Community; Genomics; Low prevalence; MRSA; Outbreaks; Humans; Methicillin-Resistant Staphylococcus aureus; Community-Acquired Infections; Staphylococcal Infections; Disease Outbreaks; Prevalence; Risk Factors; Animals